Theoretical and Experimental Investigation on Dynamic Response of Asphalt Pavement Under Vibration Compaction - Shan, Hong-Yu; Dan, Han-Cheng; Wang, Shi-Ping; Liu, Xiang; Wang, Hao (Frontiers in Materials, 2022)
This paper aims to investigate the dynamic response regulation through combining the theoretical analysis and field test under the vibration rolling condition. Based on the viscoelastic theory of multi-layer system, the dynamic stiffness method (DSM) incorporating multi-dimensional Fourier transform is proposed to solve the 3-dimentional (3D) dynamic response of pavement under vibration compaction. The stiffness matrix of each pavement layer and the global stiffness matrix of the whole pavement structure are obtained. By combining vibration load with boundary conditions, the 3D exact solution is obtained and validated by the finite element method. In addition, the field test is also conducted using a series of sensors and equipment (e.g., SmartRock sensor, acceleration sensor, temperature sensors, non-nuclear density meter) to calibrate the theoretical model to determine the wave number and dynamic modulus during the vibration rolling process. Then, considering the factors during compaction, the rules of displacement variation and pavement acceleration are investigated in terms of modulus, thickness and density. The results show that the 3D displacement and acceleration components both vibrate with high frequencies during compaction, and the peak acceleration in the vertical direction prevails. For the vertical displacement, its distribution beneath the drum of roller is almost even except that it drops to zero abruptly around drum edge. The relationship between thickness and acceleration follows a linear function, and the acceleration on pavement surface rises when the thickness increases. Although the density and modulus are increasing with the rolling times, the effect of modulus on acceleration is more obvious and prominent than that of density. In sum, the DSM presented in this paper provides a robust method to calculate the dynamic response of pavement under vibratory compaction and to back-calculate the modulus of compacted pavement layers. Moreover, the regulation also shed insight on the understanding of vibration compaction mechanism that there is a potentially strong correlation between compaction state, modulus and vibration acceleration.